2013
DOI: 10.1007/s11255-013-0442-y
|View full text |Cite
|
Sign up to set email alerts
|

Bladder function in 17β-estradiol-induced nonbacterial prostatitis model in Wister rat

Abstract: Objectives: To investigated the bladder function of nonbacterial prostatitis (NBP) rat model that was induced by the injection of 17-estradiol in castrated rats. Methods:Ten-month-old male Wistar rats were divided into 2 groups (sham vs NBP; each N=8). NBP model was experimentally induced by castration followed by daily subcutaneous injection of 17-estradiol for 30 days. On the 31st day after surgery, we investigated several parameters; (1) Voiding behavior, (2) Bladder blood flow, (3) Measurements of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
(15 reference statements)
1
3
0
Order By: Relevance
“…We did not observe any changes in voiding behavior in either model. The finding that HCP did not cause a significant change in either of these parameters is consistent with previous reports . Although we do not know the precise reason why prostatic inflammation did not result in abnormal bladder function in these two models, it is likely due to a relatively low degree of severity of the prostatic inflammation, because prostatic inflammation induced by the direct injection of irritants such as carrageenan and formalin into the prostate leads to overactive bladder, as detected by cystometry .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not observe any changes in voiding behavior in either model. The finding that HCP did not cause a significant change in either of these parameters is consistent with previous reports . Although we do not know the precise reason why prostatic inflammation did not result in abnormal bladder function in these two models, it is likely due to a relatively low degree of severity of the prostatic inflammation, because prostatic inflammation induced by the direct injection of irritants such as carrageenan and formalin into the prostate leads to overactive bladder, as detected by cystometry .…”
Section: Discussionsupporting
confidence: 91%
“…The finding that HCP did not cause a significant change in either of these parameters is consistent with previous reports. 20 Although we do not know the precise reason why prostatic inflammation did not result in abnormal bladder function in these two models, it is likely due to a relatively low degree of severity of the prostatic inflammation, because prostatic inflammation induced by the direct injection of irritants such as carrageenan and formalin into the prostate leads to overactive bladder, as detected by cystometry. 7,8 In the prostatitis model induced by injection of irritants into the dorsal lobe of the prostate, inflammation in the prostate increases macrophage infiltration and the expression of T cell markers of the bladder, and prostate-to-bladder afferent crosssensitization is a potential mechanism by which prostatitis could result in bladder overactivity.…”
Section: Discussionmentioning
confidence: 83%
“…Micturition behavior was studied at 14 days after BOO surgery as previously described . Each rat was placed in an individual metabolic cage with a 12 hr light/dark cycle for three consecutive days for acclimation.…”
Section: Methodsmentioning
confidence: 99%
“…7,8 Omegazone, a laser blood flowmeter, can be used to measure the change of blood flow induced by chemical intervention in urinary bladder. [32][33][34][35][36] In this study, we observed the accelerating effect of CRT, and quantitative evaluation should also be made using a cell counter in further steps. Despite these limitations, our findings show that CRT may attenuate damage of the urinary bladder and can be considered a prospective treatment option for OAB patients.…”
Section: Discussionmentioning
confidence: 82%